2012
DOI: 10.1073/pnas.1205270109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic gating of mechanosensitive channel of large conductance evidenced by single-subunit resolution

Abstract: Mechanosensitive (MS) ion channels are membrane proteins that detect and respond to membrane tension in all branches of life. In bacteria, MS channels prevent cells from lysing upon sudden hypoosmotic shock by opening and releasing solutes and water. Despite the importance of MS channels and ongoing efforts to explain their functioning, the molecular mechanism of MS channel gating remains elusive and controversial. Here we report a method that allows single-subunit resolution for manipulating and monitoring "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 37 publications
6
72
0
Order By: Relevance
“…Here, to open these tension-sensitive channels in our experimental setup, we used heteropentameric MscLs comprised of varying number of WT and cysteine point-mutated subunits (G22C) per pentamer ( Fig. 2) (16). Even though in nature, MscL opens in response to tension in the lipid bilayer, attaching charged cysteine-specific compounds to the pore of MscL-G22C homopentamers opens the channel spontaneously (36)(37)(38).…”
Section: Ion Mobility-mass Spectrometry Can Distinguish Individual Hementioning
confidence: 99%
See 2 more Smart Citations
“…Here, to open these tension-sensitive channels in our experimental setup, we used heteropentameric MscLs comprised of varying number of WT and cysteine point-mutated subunits (G22C) per pentamer ( Fig. 2) (16). Even though in nature, MscL opens in response to tension in the lipid bilayer, attaching charged cysteine-specific compounds to the pore of MscL-G22C homopentamers opens the channel spontaneously (36)(37)(38).…”
Section: Ion Mobility-mass Spectrometry Can Distinguish Individual Hementioning
confidence: 99%
“…We increased the hydrophilicity of the channel pore one subunit at a time using WT G22C heteropentameric MscLs. As the number of G22C subunits per heteropentamer increased, hence also the number of binding sites for positive charges within the pore constriction, the channels opened further and visited higher subconducting states (16).…”
Section: Ion Mobility-mass Spectrometry Can Distinguish Individual Hementioning
confidence: 99%
See 1 more Smart Citation
“…Site-directed fluorescence spectroscopy can also be used to identify different structural domains associated with asymmetric ligand binding (Sommer et al, 2012). Additionally, quenching experiments can be exploited in the study of membrane channels and transporters to monitor gating (Birkner, 2012) and characterize translocation pathways (Smriti et al, 2009) and conformational heterogeneity (Siarheyeva, 2010) in general.…”
Section: B Fluorescence Spectroscopymentioning
confidence: 99%
“…It was demonstrated via EPR that asymmetric incorporation of lysophosphatidylcholine into phosphatidylcholine vesicles resulted in iris-like rotation and tilt of the TM helices of MscL channels. By changing the hydrophobicity of a pore-lining TM1 moiety at the hydrophobic gate and using fluorescence labelling, it was elegantly demonstrated that the hydrophobicity of a single TM1 domain initiates MscL gating, and the contribution of other TM helices is asymmetric (Birkner et al, 2012). This type of asymmetric perturbation of membrane lipids and MscL by phospholipase A 2 has been recently exploited to engineer signalling networks (Charalambous et al, 2012).…”
Section: C Pentameric Ligand-gated and Mechanosensitive Channelsmentioning
confidence: 99%